Security measures to ensure the intellectual property protection of internet-based publications - Tirado, Kenneth C.; Cabbab, Johann Frederick A. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2001)
Information available on the Internet are more often left unprotected in terms of intellectual property. As Internet technology becomes a common mode for people to access information, it is assumed that in the future a virtual library will emerge to cater to the needs of the public. Whatever we do, things are bound to go wrong. There isn't a single security system that is perfect. Petty theft can get away for as long as the thief is fast and careful. What we need is vigilance and determination to fulfill our duties and protect what we treasure.
The key to a solid protection of works published on the Internet is the cooperation between all parties involved. A mutual understanding on the limitations of the users' access would provide planners and developers with a better guide for preparing security and protection of their works. Close coordination with the proper authorities and proper understanding of the laws will aid in solving aberrations more quickly.
Vita.
Thesis (Bachelor of Library and Information Science)
Keywords: Intellectual property; Internet (Computer network).